2014
DOI: 10.1093/bja/aet307
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid or colloid for goal-directed fluid therapy in colorectal surgery

Abstract: Goal-directed fluid therapy is possible with either crystalloid or HES. There is no evidence of a benefit in using HES over crystalloid, despite its use resulting in a lower 24 h fluid balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 30 publications
5
142
1
8
Order By: Relevance
“…They found no difference in outcomes although, similar to a previous study, 60% more fluid was needed in the crystalloid group [73]. Therefore, in clinical practice without significant hypovolemia, the colloid-to-crystalloid ratio appears to be approximately 1:1.5 [72,73]. However, the volume effect of colloids is context sensitive [14], and when hypovolemia is present, the colloid-to-crystalloid ratio may be higher [71].…”
Section: Recent Studies Of Gdft Within An Enhanced Recovery Programsupporting
confidence: 61%
See 1 more Smart Citation
“…They found no difference in outcomes although, similar to a previous study, 60% more fluid was needed in the crystalloid group [73]. Therefore, in clinical practice without significant hypovolemia, the colloid-to-crystalloid ratio appears to be approximately 1:1.5 [72,73]. However, the volume effect of colloids is context sensitive [14], and when hypovolemia is present, the colloid-to-crystalloid ratio may be higher [71].…”
Section: Recent Studies Of Gdft Within An Enhanced Recovery Programsupporting
confidence: 61%
“…Yates et al recently conducted an RCT comparing the use of boluses of crystalloid or colloid for GDFT during major surgery [72]. They found no difference in outcomes although, similar to a previous study, 60% more fluid was needed in the crystalloid group [73].…”
Section: Recent Studies Of Gdft Within An Enhanced Recovery Programmentioning
confidence: 65%
“…A recent study comparing crystalloids with colloids for fluid boluses within a GDFT algorithm found no difference in the primary outcome of postoperative GI morbidity at postoperative day five. 64 Nevertheless, there was a significantly higher 24-hr positive fluid balance in the crystalloid group, and 38% of patients in this group required a rescue colloid bolus (median volume 750 mL). There was also minimal blood loss in both groups, which is the setting in which a colloid may be most beneficial.…”
Section: Which Fluid Should I Use?mentioning
confidence: 85%
“…Although in a different patient population, this has prompted further investigation of the issue of crystalloid versus colloid in perioperative GDT. Studies comparing crystalloid-versus colloid-based GDT in both colorectal 82 and neurosurgical 83 procedures have demonstrated lower IV fluid volumes in colloid-based GDT patients without any meaningful clinical differences between the 2 groups. A study comparing balanced crystalloid-versus colloid-based GDT algorithms in patients undergoing cytoreductive surgery for primary ovarian cancer demonstrated lower volumes of intravenous fluids, higher CO, and higher SV in colloid patients, though they found no differences in postoperative complications of LOS.…”
Section: Fluidsmentioning
confidence: 99%